Acidic Properties of CoCl2+6H2O and NiCl2+6H2O Microwave Ion Exchanged NaY Zeolite - ZENDEHDEL, M.; AMINI, M.M.; EMAMI KHANSARI, M. (Asian Journal of Chemistry, 2010)
The acidity of NaY zeolite was modified with CoCl2·6H2O and NiCl2·6H2O by microwave irradiation solid state ion exchange method. The acidity of modified zeolite was investigated by thermal analysis (TGA/DSC) and Fourier transform infrared (FTIR) spectroscopy after pyridine chemisorbed on metal/zeolites. The results showed that in the microwave irradiation solid state ion exchanged zeolites, the Lewis acid sites are dominant acidic sites.